Integration of Business Intelligence in Data Lake Solutions - Nandish Shivaprasad, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Data lakes with BI allows organizations to effectively navigate the advantages of unstructured, semi unstructured and structured data. This paper therefore focuses on BI technologies in data lakes, with especial consideration to the challenges, integration techniques, and the technologies that enable appropriate interoperation. Successful BI in data lakes: Hadoop and Spark as distributed computing frameworks; cloud platforms; and data integration tools. However, the need to develop suitable solutions for integrating such enterprise applications is still a work in progress because of issues like data quality, data governance, and data accessibility on the same.
Keywords: Business Intelligence; Big Data; Distributed Systems; Cloud Environment